Addressing Lupus Health Disparities: The MONARCAS Community and Academic Collaborative Program - Karen Mancera-Cuevas; Patricia Canessa; Joan S. Chmiel; Elizabeth A. Hahn; Anh H. Chung; Daniel L. Erickson; Rosalind Ramsey-Goldman (Mary Ann Liebert, 2018)
Purpose: The Centers for Disease Control (CDC) Popular Opinion Leader (POL) model was implemented in a lupus education program (MONARCAS) for the Latino community. The program aim was to increase lupus awareness by training high school students, community health workers, and parents. Methods: A curriculum was developed training POLs to disseminate concepts about lupus signs and symptoms. Pre- and post-program questions assessed lupus knowledge and message dissemination. Results: POL groups represented distinct demographic characteristics with Spanish or English language dominance. POLs reported increased lupus knowledge and program satisfaction. Conclusions: Future program goals should aim to increase understanding and improving access to care for Latino communities affected by lupus.